Pengaruh Modernisasi Terhadap Hukum Waris Adat Batak Karo - Arman Arroisi Hatta; Josua Arya Subagiyo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Karo Batak customary inheritance law is based on a patrilineal system which determines that the main heir is the eldest son. However, it should be noted that women also have the right to inheritance in some cases, especially if there are no sons in the family. In general, inherited assets are divided equally between the children and surviving spouse of the deceased, but certain properties such as land or inherited property in particular are more likely to be passed patrilineally to the eldest male child to maintain the continuity of the bloodline. This system also recognizes the important role of ancestors in determining inheritance distribution and has strong customary mechanisms to resolve conflicts that may arise regarding inheritance distribution. Even though it is still recognized and implemented, Karo Batak customary inheritance law has faced several challenges and adaptations with the advent of the modern era. Changing living patterns, urbanization, greater education, and the influence of national laws often influence the way heritage is managed and shared. In many cases, inheritance arrangements may combine elements of customary law with national law to adapt to social changes and the practical needs of modern families. This could have the impact of a more equal distribution between children, without necessarily taking into account gender or birth order, as well as paying more attention to the economic and social needs of family members. Despite this, customary inheritance law practices are still respected and maintained in many Karo Batak communities, often as part of their cultural identity and traditions.